Writing In College From Competence to Excellence - Guptill, Amy (Open textbook library., 2016)
Writing in College is designed for students who have largely mastered high-school level conventions of formal academic writing and are now moving beyond the five-paragraph essay to more advanced engagement with text. It is well suited to composition courses or first-year seminars and valuable as a supplemental or recommended text in other writing-intensive classes. It provides a friendly, down-to-earth introduction to professors' goals and expectations, demystifying the norms of the academy and how they shape college writing assignments. Each of the nine chapters can be read separately, and each includes suggested exercises to bring the main messages to life. Students will find in Writing in College a warm invitation to join the academic community as novice scholars and to approach writing as a meaningful medium of thought and communication. With concise discussions, clear multidisciplinary examples, and empathy for the challenges of student life, Guptill conveys a welcoming tone. In addition, each chapter includes Student Voices: peer-to-peer wisdom from real SUNY Brockport students about their strategies for and experiences with college writing. While there are many affordable writing guides available, most focus only on sentence-level issues or, conversely, a broad introduction to making the transition. Writing In College, in contrast, provides both a coherent frame for approaching writing assignments and indispensable advice for effective organization and expression.